2022
DOI: 10.1038/s43587-022-00293-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune system-wide Mendelian randomization and triangulation analyses support autoimmunity as a modifiable component in dementia-causing diseases

Abstract: Immune system and blood–brain barrier dysfunction are implicated in the development of Alzheimer’s and other dementia-causing diseases, but their causal role remains unknown. We performed Mendelian randomization for 1,827 immune system- and blood–brain barrier-related biomarkers and identified 127 potential causal risk factors for dementia-causing diseases. Pathway analyses linked these biomarkers to amyloid-β, tau and α-synuclein pathways and to autoimmunity-related processes. A phenome-wide analysis using Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…In most cases, autoimmune diseases are treated with longterm anti-inflammatory or immunosuppressive medications. This may mean that the small IRRs observed in our study are masked by the effect of medications either by suppressing severe inflammation (hence, inflammation per se was not assessed in our study) or reducing dementia risk, as suggested in some studies 34,37,38 (albeit with inconclusive evidence). To acknowledge this, we…”
Section: Strengths and Limitationsmentioning
confidence: 73%
See 3 more Smart Citations
“…In most cases, autoimmune diseases are treated with longterm anti-inflammatory or immunosuppressive medications. This may mean that the small IRRs observed in our study are masked by the effect of medications either by suppressing severe inflammation (hence, inflammation per se was not assessed in our study) or reducing dementia risk, as suggested in some studies 34,37,38 (albeit with inconclusive evidence). To acknowledge this, we…”
Section: Strengths and Limitationsmentioning
confidence: 73%
“…Other limitations common to observational and registry-based studies include residual confounding from lifestyle differences and validity of diagnostic codes. We also did not have genetic data, which are likely to play an important role in the associations under investigation . Furthermore, it is not possible to conclude whether the dose-response association is present in both the short and long term, because we assessed this regardless of the timing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The more than 11,000 FG participants with a probable diagnosis AD at start of our study represent about 8% of prevalent dementia and AD cases in Finland (20). As a research cohort, these individuals already contributed to improve the understanding of the genetic etiology of AD (27,28). Utilizing research data from this cohort for a clinical recall study required thorough collaboration between the study investigators and BEF over a period of nearly two years from first contact to study completion.…”
Section: Discussionmentioning
confidence: 99%